Exploring medical first responders’ perceptions of mass casualty incident scenario training: a qualitative study on learning conditions and recommendations for improvement - Quynh Nguyen; Lina Gyllencreutz; Fredrik Schulz; Anke Baetzner; David Sjöberg (BMJ Open)
Objective Despite participating in scenario training, many medical first responders (MFRs) perceive themselves as inadequately prepared to respond to mass casualty incidents (MCIs). The objective of this study was to conduct a comprehensive examination of traditional MCI scenario training methods, focusing on their inherent strengths and limitations. An investigation into the perceptions of MFRs who had participated in MCI scenario training was carried out to identify potential areas for improvement and provide recommendations for refining MCI training protocols.Design Qualitative inductive approach using semistructured interviews that took place between October 2021 and February 2022. Data were analysed with qualitative content analysis.Setting MCI scenario training involving four organisations (three emergency medical services and one search-and-rescue organisation) tasked with responding to MCIs, collectively representing four European Union countries.Participants 27 MFRs (17 emergency medical services personnel and 10 search-and-rescue volunteers) were recruited to participate in the study.Results Two categories and seven associated subcategories (shown in parentheses) were identified as influencing the learning outcomes for MFRs: Training in a context mirroring real-world incidents (conducting incident scene risk assessment, realistic representation in casualties, incorporating scenario variety into the curriculum, interagency collaboration, role alignment when training incident site management) and use of a pedagogical framework (allowing for mistakes, the importance of post-training evaluation).Conclusions This study reaffirms the value of traditional MCI scenario training and identifies areas for enhancement, advocating for realistic scenarios, interagency collaboration, improved incident site management skills and thorough post-training evaluation. It suggests a shift in MCI training conceptualisation and delivery. The potential of virtual reality technologies as a valuable addition to training methods is explored, with a note on the need for further research to ascertain the long-term effectiveness of these technologies. However, the selection of a training method should consider programme goals, target population and resources.